Effectiveness of Redd + Implementation Through FCPF-CF on Welfare in Teluk Sulaiman - Mukhaimin, Farros Syahin Fadhil Al; Amin, Khoirul; Farauqi, Mohammad Dziqie Aulia Al (Cv. Syntax Corporation Indonesia, 2026)
Indonesia's tropical forests play a crucial role in global climate regulation, yet they continue to face deforestation and degradation pressures. The REDD+ (Reducing Emissions from Deforestation and Forest Degradation) mechanism, supported by initiatives such as the Forest Carbon Partnership Facility – Carbon Fund (FCPF-CF), has been introduced to link forest conservation with local welfare improvement. This study examines the effectiveness of REDD+ implementation through FCPF-CF on welfare in Teluk Sulaiman. It investigates shifts in tree coverage, villager involvement, and changes in household income and employment. We combined several methods to gather data: interviews with 150 household leaders, in-depth discussions with key stakeholders, and reviews of existing project records. Results suggest that forest loss dropped by 23% over five years, while average household earnings rose by 7%, thanks to new employment options such as beekeeping and ecotourism. Still, several hurdles emerged, including uneven benefits across groups, poor intersectoral coordination, and low skill levels within communities. The research concludes that carbon projects work best when stakeholders are included from the start, benefits are shared transparently, and local capacities are continuously strengthened.